2012
DOI: 10.1142/s0219581x12400364
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Imidacloprid From Poly (Styrene–diacetone Crylamide)-Based Nanoformulation

Abstract: Imidacloprid is a neonicotinoids insecticide, which is important for the cash crops such as tomato, rape and so on. The conventional formulation does not only increase the loss of pesticide but also leads to environmental pollution. Controlled-release formulations of pesticide are highly desirable not only for attaining the most effective utilization of the pesticide, but also for reducing environmental pollution. Pesticide imidacloprid was incorporated in poly (styrene–diacetone crylamide)-based formulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For example, poly(ε-caprolactone) is an aliphatic polyester that is insoluble in water, biodegradable, and biocompatible, amongst other useful physicochemical properties 15 16 . This polymer can be used to synthesize the nanocapsules possessing an oily interior that are capable of efficiently encapsulating hydrophobic compounds including tebuconazole and carbendazim 17 18 19 . Solid lipid nanoparticles (SLNs) are other promising carrier systems are that can be used to transport nonpolar substances whose mobility is restricted by interaction with the lipids, resulting in modified release profiles 20 21 .…”
mentioning
confidence: 99%
“…For example, poly(ε-caprolactone) is an aliphatic polyester that is insoluble in water, biodegradable, and biocompatible, amongst other useful physicochemical properties 15 16 . This polymer can be used to synthesize the nanocapsules possessing an oily interior that are capable of efficiently encapsulating hydrophobic compounds including tebuconazole and carbendazim 17 18 19 . Solid lipid nanoparticles (SLNs) are other promising carrier systems are that can be used to transport nonpolar substances whose mobility is restricted by interaction with the lipids, resulting in modified release profiles 20 21 .…”
mentioning
confidence: 99%
“…The regulated release of the formulation also leads to reduced number of applications. Qian et al (2013) reported the controlled release formulation of imidacloprid by incorporating it in poly (styrene-diacetone acrylamide). The results exhibited that the formulation at higher temperature and more diacetone acrylamide had lower value of T 50 , indicating quicker release of the active ingredient under the conditions.…”
Section: Polysaccharides Based Nanoformulationsmentioning
confidence: 99%
“…14−16 This is because of the difficulty in generating stable nanosuspensions with controlled particle size distribution and higher cost in processing to prepare. 17 Lignin is a unique renewable natural aromatic polymer, as well as the second most abundant component in plants, which contains many reactive groups such as phenolic hydroxyl groups, carbonyl groups, conjugated double bonds, and sulfonate groups, depending on the type, 18,19 and displays excellent antioxidant, antiultraviolet, and biodegradable properties because of its aromatic nature. 20 Lignin has been widely used in the research of controlled release pesticides as biopolymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the traditional formulations of pesticides, nanoformulations have a smaller particle size, higher specific surface area, and offer better leaf coverage, lower application rates, UV protection, controlled release, increased bioavailability, and reduction of the influence on the environment on bioavailability variability. However, despite controlled release nanoformulation technology in drug delivery being well-established, its application in agriculture is still underdeveloped. This is because of the difficulty in generating stable nanosuspensions with controlled particle size distribution and higher cost in processing to prepare …”
Section: Introductionmentioning
confidence: 99%